Process standardization for manufacture of Ready-to-Reconstitute Carrot Halwa mix - Modha, Hiralkumar M; Vaghela, Nilesh R; Gokhale, Ajay J; Patel, Amit M; Patel, H G (Indian Journal of Dairy Science, 2016)
Carrot halwa is popular traditional Indian sweet delicacy and widely consumed, but it is time consuming to prepare it. To make it instantly available with minimum requirements and for industrial production of popular sweetmeat an optimized process is needed. Thus, method of manufacture of ready-to-reconstitute (RTR) Carrot halwa mix was optimized. The rate of addition of khoa, ghee and sugar in the range of 0-30 %, 0-6 % and 25-40 % respectively were studied and optimum values determined using the Central Composite Rotatable Design of Response Surface Methodology. Optimized product developed with roasting of blanched carrot shreds in 1.22 % ghee with addition of 23.92 % grated khoa by weight of blanched shreds with continuous and gentle mixing and heating till pat formation stage, and then spreaded in SS tray and dried in Vacuum Tray Dryer. The dehydrated RTR Carrot Halwa mix then rehydrated using hot water (85á´¼C) with ratio of 1:2 with mixing as and when required for sensory evaluation. In this rehydrated mass 36.96 % sugar by weight of rehydrated product is added with gentle heating and mixing. The optimized product was found to contain 5.08% moisture, 26.11% fat, 19.33% total protein, 4.99% ash and 44.48% total carbohydrates. The pH, acidity (%LA), total carotenoids (mg/kg), water activity and TBA value were 6.73, 0.43, 43.07, 0.32 and 0.120 respectively. Standard plate count was observed to be 2.57 log cfu. Yeast & Mold, Coliform, E. coli, Salmonella, Staphylococcus aureus and ListeriaÂ monocytogenes were absent in product.